A 'year in the life' of health services research in oncology. (October 2012) - Brundage, Michael D; Snyder, Claire F; Bass, Brenda
Oncology health services research (HSR) is a broad, multidimensional field. Current areas of research foci may be informative. We searched Medline for oncology HSR papers published in English in a single year (2009). Abstracted data related to access, quality, cost, health/wellbeing, place on the cancer continuum and study design. Among 1113 papers, the most commonly studied HSR domain was quality-of-care (65%). Within the care continuum, 'treatment' received the greatest attention (37%), and 'prevention' the least (5%). More specifically, treatment-related quality-of-care was most often studied (23%). Breast cancer was the most common site focus (28%). Most studies were descriptive (75%), retrospective (35%) or cross-sectional (35%). These findings might inform the decisions of researchers or policy makers seeking to improve cancer health services delivery.